2021
DOI: 10.3390/fermentation7040227
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus velezensis Identification and Recombinant Expression, Purification, and Characterization of Its Alpha-Amylase

Abstract: Amylases account for about 30% of the global market of industrial enzymes, and the current amylases cannot fully meet industrial needs. This study aimed to identify a high α-amylase producing bacterium WangLB, to clone its α-amylase coding gene, and to characterize the α-amylase. Results showed that WangLB belonged to Bacillus velezensis whose α-amylase gene was 1980 bp coding 659 amino acids designated as BvAmylase. BvAmylase was a hydrophilic stable protein with a signal peptide and a theoretical pI of 5.49.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
(97 reference statements)
0
1
0
Order By: Relevance
“…The bacterial lysates were checked using a sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE), and a protein band of the expected molecular weight in the expressed proteins of the bacteria confirmed the fusion protein expression. The experimental process is similar to that described by Zhang et al [ 45 ].…”
Section: Methodsmentioning
confidence: 78%
“…The bacterial lysates were checked using a sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE), and a protein band of the expected molecular weight in the expressed proteins of the bacteria confirmed the fusion protein expression. The experimental process is similar to that described by Zhang et al [ 45 ].…”
Section: Methodsmentioning
confidence: 78%
“…In this work, we found that most of the Bacillaceae strains displayed the amylase-producing ability in the artifcial ponds and earthen ponds, particularly the genera of Bacillus and Halobacillus. Numerous Bacillus species were identifed as the producer of amylases, such as B. licheniformis [41], B. amyloliquefaciens [42], B. subtilis [43], B. cereus [44], B. paramycoides [45], B. koreensis [46], and B. velezensis [47]. At the same time, there were relatively few reports on Halobacillus species with the capacity of producing amylases, such as Halobacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…The α-amylase gene from B. velezensis WangLB was cloned, expressed, purified, and characterized. The purified α-amylase maintained high activity over a wide range of temperatures [30] . A novel fibrinolytic serine metalloprotease gene and a galactosidase gene from B. velezensis SW5 were heterologously expressed in E. coli [31][32] .…”
Section: Bioinformatics Study Of B Velezensismentioning
confidence: 97%